Research and application of forward three-dimensional design method of substation. Issue 1 (1st December 2022) - Xu, Wenzhe; Shi, Jiabing; Sun, Zhengzhu; Lv, Shudong; Fang, Junqi; Li, Wenting; Lv, Lei; Ni, Yuxiang
Abstract: During the operation of digital substations, they are vulnerable to the influence of different fault feature extraction, resulting in weak anti-interference in the detection process. To solve this problem, the singular value decomposition method is combined detection method to establish a prediction model. Firstly, the three-dimensional control mode model is established based on mathematical method to process the current signal with anti-interference; Secondly, the singular value method is used to optimize the current transmission process and denoise the fault signal feature extraction; Finally, the method of singular value decomposition is used to realize fault detection in substation operation.